Asymmetric flexural process and fracture behaviors of natural bamboo node with gradient discontinuous fibers. (April 2021) - Chen, Guowei; Luo, Hongyun
Abstract: Natural bamboo node samples bended from two opposite radial directions (Type I and Type II) displayed asymmetric flexural fracture process and behaviors. The real-time flexural process and fracture behaviors were observed and analyzed with the aid of optical video microscopy and acoustic emission (AE). Results indicated there are three kind of fracture behaviors within bamboo node during the deformation and fracture process, which are parenchyma cells failure, fiber dissociation and fiber breakage. They showed different sequences due to the gradient discontinuous fibers within bamboo node. The toughening mechanisms within bamboo node are concluded as cellular-fibrous effect, crack deflection, fiber bridging/pull-out and the induced avalanche delay. Highlights: Bamboo node has gradient discontinuous fibers. Bamboo node shows asymmetric flexural fracture process and behaviors. In situ video microscopy and acoustic emission were co-applied. Toughening effects inspired by bamboo node are discussed.